2016
DOI: 10.18273/revsal.v48n2-2016002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasitic infections in preschool-children from vulnerable neighborhoods in Bogotá

Abstract: Introduction:Intestinal parasitic infections (IPIs) are neglected tropical diseases, even though their prevalence is high in many developing countries. The public health impact of IPIs is substantial, in particular for children due to the negative effect on growth and development. Objectives: This study examines the prevalence and risk factors of IPIs in preschool-children from at-risk neighborhoods, including those from internally displaced families. Materials and Methods: A cross-sectional study among 239 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…This study reported that 57 of 224 (25.4%; 95% CI = [20.2, 31.1]) children had intestinal parasitic infection, which was lower than the findings of studies in Wondo Genet (85.1%), 31 Hawassa Zuria District (51.3%), 32 Southern Ethiopia (41.9%), 33 and Chuahit (35.2 %). 34 The prevalence reported by this study was similar to the findings in Wonji Shoa Sugar Estate (24.3%) 35 and Butajira town (23.3%) 36 ; Sudan (24.9%) 37 ; 20 ; and Diamantina, Brazil (27.5%). 18 The current prevalence is also higher than the finding of a study in Nigeria (13.7%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study reported that 57 of 224 (25.4%; 95% CI = [20.2, 31.1]) children had intestinal parasitic infection, which was lower than the findings of studies in Wondo Genet (85.1%), 31 Hawassa Zuria District (51.3%), 32 Southern Ethiopia (41.9%), 33 and Chuahit (35.2 %). 34 The prevalence reported by this study was similar to the findings in Wonji Shoa Sugar Estate (24.3%) 35 and Butajira town (23.3%) 36 ; Sudan (24.9%) 37 ; 20 ; and Diamantina, Brazil (27.5%). 18 The current prevalence is also higher than the finding of a study in Nigeria (13.7%).…”
Section: Discussionsupporting
confidence: 87%
“…The parasitic relation of worms with human has been influenced by global changes in the human sociocultural spectrum. 13,14 Socioeconomic factors, like income or poverty, 8,15-18 occupation especially farming and fishing, 8,18-20 number of siblings, 16,20 age of children, 19,21,22 family size, 19,20 households educational status, 19,23 and health supervision or provision of health education 24,25 are contributing for persistent transmission of the parasitic disease.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important given that treatment programs for intestinal parasites in Colombia are not aimed at the preschool-age population and do not include treatment for intestinal protozoa. 4,5 Moreover, prevalence data generated from this study provides evidence for local decision making for implementing resources to improve living conditions for urban and rural populations of children in Colombia. 14,19 A major limitation of this study was the lack of G. intestinalis assemblages and Blastocystis subtype identification.…”
mentioning
confidence: 88%
“…17 The high prevalence of intestinal parasites found in the study population confirms that childhood intestinal parasitic infections are a relevant health issue in both urban poor and rural communities in Colombia and serves as an important indicator of community-level socioeconomic development. 8,10 Because accurate prevalence data in a region or community is essential for identifying local vulnerabilities, 4,17,19 molecular epidemiologic data from this study provides evidence of important community needs common to both urban slum and rural communities included in this study. Accurate epidemiologic data from this study is also critical for treatment decisions in mass drug administration programs, impact evaluation, and surveillance.…”
mentioning
confidence: 95%
See 1 more Smart Citation